Developing an activity design model for assessing teachers' mathematical understanding - Görgüt, Rahime Çelik; Dede, Yüksel (Elsevier BV, 2023)
© 2022 Elsevier LtdThis study indented to develop an activity design model to assess mathematical understanding. For this purpose, the Assessing mathematical understanding [AMU] Model was designed using the design experiment method. A fourteen-week study with pre-service mathematics teachers determined by convenience sampling and criterion sampling methods revealed the pre-service teachers' mathematical understanding skills and the phases of the AMU Model. The data were collected through the course activities designed independently by the pre-service mathematics teachers for assessing mathematical understanding and the activity assessment forms designed by the researchers and applied to the pre-service teachers. Data were analyzed using ongoing analysis and retrospective analysis. Results revealed that pre-service mathematics teachers' skills for assessing mathematical understanding improved with the AMU Model, which consists of interrelated phases such as self-assessment, peer -assessment, whole-class discussion, and sample video recordings. Some suggestions for further research were also made based on the results.
Keywords: 4. Education